Clinicopathological, immunohistochemical charachtaristic and the outcome of Hodghkin lymphoma patients in Erbil city, Iraq - Lilan Bahzad Mohammedzaki; Kawa Muhammedamin Hasan; Ranan Kardagh Polus; Ahmed Khudair Yassin (Iraqi Journal of Hematology, 2019)
BACKGROUND: Hodgkin lymphoma (HL) has unique epidemiological features with diversified pathologies and exhibits considerable clinicopathological variations in different parts of the world. OBJECTIVES: We aimed in this study to assess clinic-pathological features, immunohistochemistry and outcome of HL patients treated in Erbil, northren Iraq. PATIENTS AND METHODS: This was a retrospective study conducted in Nanakaly Hospital for blood diseases and oncology in Erbil, North Iraq; a total of 125 patients diagnosed between January 2012 and December 2016 were involved; they were assessed for their clinical characteristics and histopathology and immunophenotyping findings and their outcome was evaluated as well. RESULTS: The median age was 28 years (range: 18–71 years); 55% were male and 41% had Stage II disease; common histological type is nodular sclerosis (51.2%) followed by mixed cellularity (43.2%); CD30 was positive in nearly all cases of classical HL, and CD15 was positive in 98.7% and CD20 was positive in 75% in nodular lymphocyte predominant subtype. Most of the patients received adriamycin, bleomycin, vinblastine, and dacarbazine chemotherapy, and the 5-year overall survival in our study is 70%. Advanced stage (IV), high lactate dehydrogenase level, low hemoglobin, and splenomegaly are significant predictors for poor survival. CONCLUSION: Our patient exhibited outcomes that were lower to those reported in developed countries.